2017
DOI: 10.5194/amt-10-1079-2017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of snowfall accumulation underestimation by tipping bucket gauges in the Spanish operational network

Abstract: Abstract. Within the framework of the World Meteorological Organization Solid Precipitation Intercomparison Experiment (WMO-SPICE), the Thies tipping bucket precipitation gauge was assessed against the SPICE reference configuration at the Formigal-Sarrios test site located in the Pyrenees mountain range of Spain. The Thies gauge is the most widely used precipitation gauge by the Spanish Meteorological State Agency (AEMET) for the measurement of all precipitation types including snow. It is therefore critical t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 26 publications
0
60
0
1
Order By: Relevance
“…However, ρ HN values span a wide range, and values from 10 to 350 kg m −3 have been reported from American and European mountain ranges, with mean values between 70 and 110 kg m −3 (e.g. Diamond and Lowry, 1954;LaChapelle, 1962;Power et al, 1964;Judson, 1965;McKay et al, 1981;Meister, 1985;Judson and Doesken, 2000;Valt et al, 2014). Most of the ρ HN data analysed in these studies were observed using readings on a snow board.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, ρ HN values span a wide range, and values from 10 to 350 kg m −3 have been reported from American and European mountain ranges, with mean values between 70 and 110 kg m −3 (e.g. Diamond and Lowry, 1954;LaChapelle, 1962;Power et al, 1964;Judson, 1965;McKay et al, 1981;Meister, 1985;Judson and Doesken, 2000;Valt et al, 2014). Most of the ρ HN data analysed in these studies were observed using readings on a snow board.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies analysed ρ HN values on a daily basis and confirmed this 10 : 1 rule as applicable for a first estimate (e.g. Roebber et al, 2003;Egli et al, 2009;Teutsch, 2009). However, ρ HN values span a wide range, and values from 10 to 350 kg m −3 have been reported from American and European mountain ranges, with mean values between 70 and 110 kg m −3 (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The collection efficiency of precipitation gauges is influenced by the wind speed and a bias adjustment for solid precipitation is needed under windy conditions Buisán et al, 2017;Smith et al, 2017;Pan et al, 2016). Measurement errors due to gauge undercatch frequently range between 20 and 50 % .…”
Section: Correcting For Geonor Undercatchmentioning
confidence: 99%